Choose your collaborators wisely: Addressing interdependent tasks through collaboration in responding to wildfire disasters. (12th July 2022) - Bodin, Örjan; Guerrero, Angela M.; Nohrstedt, Daniel; Baird, Julia; Summers, Robert; Plummer, Ryan; Jasny, Lorien
Abstract: Responding to disastrous wildfires traversing geographical scales requires multi‐actor collaboration to address a series of interdependent operational tasks. While this type of distributed collective action problem is salient across governance contexts, less is known about if and how collaboration helps individual actors effectively address their tasks. Applying a novel network‐centric method to wildfire responder networks in Canada and Sweden, this study shows that when actors working on the same tasks collaborate, and/or when one actor addresses two interdependent tasks, effectiveness increases. The number of collaborative ties an actor has with others does not enhance effectiveness. Furthermore, when the chain of command is unclear, and/or when actors lack recent disaster management experience and/or pre‐existing collaborative relationships, effectiveness only increases if multiple actors collaborate over multiple interdependent tasks. The results have implications for disaster response agencies, and they provide valuable insights for collaborative responses to significant societal and environmental challenges.